Beyond technical skill: the impact of the big five personality traits on auditor performance in a supreme audit institution - Ilhamsyah Al Rasyid; Poppy Sofia Koeswayo; Citra Sukmadilaga (Jurnal Konseling dan Pendidikan, 2026)
This study examines the extent to which the Big Five personality traits influence auditor performance in the public sector, focusing on auditors of the Audit Board of the Republic of Indonesia (BPK RI) Representative Office of West Java Province. A quantitative survey design was employed, involving 47 auditors selected through a census approach. Personality traits were measured using the IPIP-BFM-25 instrument, while auditor performance was assessed across five dimensions: audit quality, timeliness, professionalism, competence, and effectiveness of audit follow-up. Data were analyzed using descriptive statistics and multiple regression analysis to determine both partial and simultaneous effects. The results demonstrate that Conscientiousness (β = 0.653, p < 0.05), Extraversion (β = 0.987, p < 0.01), Agreeableness (β = 0.989, p < 0.01), and Openness to Experience have significant positive effects on auditor performance. In contrast, Neuroticism shows a significant negative effect (β = −1.359, p < 0.001). Simultaneously, the Big Five personality traits explain 67.8% of the variance in auditor performance, indicating a strong explanatory power of personality factors in predicting performance outcomes. These findings suggest that public sector audit institutions should integrate personality-based considerations into auditor recruitment, placement, and capacity development to improve audit effectiveness and accountability. This study adds empirical value by quantitatively linking personality psychology with public sector audit performance within the context of Indonesia’s supreme audit institution.